Prototipe Rancangan Pembelajaran Matematika Untuk Siswa Sekolah Dasar - Ferryka, Putri Zudhah; Rofisian, Nela (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2022)
This study aims to explain the procedure for developing prototypes and producing quality prototypes for learning Mathematics in Elementary Schools. The research method used is Research and Development (R&D). The prototype was prepared using Sugiyono's six development steps including: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trials. Data collection techniques used were interviews and questionnaires. The results of the questionnaire which were distributed to 22 students in grade 15 of SD, the researcher obtained data that 60% of students had difficulty understanding fractional material. From these data the researcher was motivated to relate the material containing the concept of fractions to the song. Prototypes are validated by experts and practitioners. The average score of the three validators is 3.5 in the "very good" category, so it's worth testing. Limited trials were conducted by researchers to 22 fourth grade elementary school students. From the results of the evaluation, the researchers obtained data that 90.9% of students scored above the KKM for addition and subtraction of whole numbers. From the results of reflection, students are happy to learn fractional material using song media. The quality of the thematic Mathematics learning design for fractional materials using song media is included in the very good criteria and is appropriate for students' understanding. included in the very good criteria and feasible to use. This was obtained based on the results of validation by mathematicians 3.15, from music experts it was 3.41 and from grade IV elementary school teachers it was 3.21. The average validation result of the three validators is 3.25.